Pancreas damage and intratracheal NiCl2 administration. Effects of nickel chloride. - Novelli, E. L.; Sforcin, J. M.; Rodrigues, N. L.; Ribas, B. O. (My University, 1990)
Changes in activities of Cu-Zn superoxide dismutase (SOD- E.C.1.15.1.1.) and lactate dehydrogenase (LDH- E.C.1.1.1.27.) and levels of copper, total protein, triglycerides, phospholipids and total lipids were investigated in pancreas of rats after intratracheal administration of NiCl2 (8.4 mumol/kg). Nickel chloride induced increased SOD activity in pancreas and erythrocytes. This elevation was related to increased copper and decreased phospholipid content in pancreas of these animals. In conclusion, the ability of an animal to tolerate nickel chloride induced damage was governed by a delicate balance between the generation of cytotoxic agents and the various pancreas defense capabilities.
Keywords: copper; free radical; lactate dehydrogenase; lipid; nickel; nickel chloride; protein; superoxide; superoxide dismutase; animal; chemistry; drug effect; enzymology; injection; male; metabolism; pancreas; rat; rat strain; trachea; Animal; Copper; Free Radicals; Injections; Lactate Dehydrogenase; Lipids; Male; Nickel; Pancreas; Proteins; Rats; Rats, Inbred Strains; Superoxide Dismutase; Superoxides; Support, Non-U.S. Gov't; Trachea